suppose i have 2 bayesian networks....

a->b and c->d ie b depends on a and d depends on b

now P(a,b,c,d)=P(a)*P(b|a)*P(c|a,b)*P(d|a,b,c)

=P(a)*P(b|a)*P(c)*P(d|c)

Am i right...?

please reply..i need it as quickly as possible...

Printable View

- Jul 10th 2011, 09:08 AMprashantgolu2 bayesian networks
suppose i have 2 bayesian networks....

a->b and c->d ie b depends on a and d depends on b

now P(a,b,c,d)=P(a)*P(b|a)*P(c|a,b)*P(d|a,b,c)

=P(a)*P(b|a)*P(c)*P(d|c)

Am i right...?

please reply..i need it as quickly as possible...